Strengthening Ecological Awareness through the Pancasila Student Profile Project: Evidence from a Private Senior High School in Medan - Nora Khairani; Nuriza Dora (MASI Mandiri Edukasi, 2025)
This study investigates the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme of Sustainable Lifestyle at SMAS Budisatrya Medan. Rising waste accumulation and declining ecological awareness among students underscore the need for educational intervention. The research specifically aims to describe how P5 is carried out and how students, teachers, and the school perceive its impact. Using a qualitative approach through observation, interviews, and documentation, the study engaged students, teachers, and the principal as participants. The findings show that students actively participated in waste sorting, recycling, and reforestation, which nurtured ecological awareness and values of discipline, responsibility, and cooperation. Teachers highlighted that P5 was more effective than conventional classroom learning because it provided direct experiential engagement, although limited facilities, time constraints, and uneven motivation were noted as challenges. The principal emphasised that P5 aligned with the school’s vision of fostering environmentally responsible characters but required family and community reinforcement. In conclusion, this study proves that P5 enhances ecological awareness and strengthens character formation through experiential learning, with sustainability hinging on wider stakeholder involvement.